Effect of withering process on the evolution of phenolic acids in winegrapes: A systematic review. (October 2021) - Scalzini, Giulia; Giacosa, Simone; Río Segade, Susana; Paissoni, Maria Alessandra; Rolle, Luca
Abstract: Background: Withering processes have a strong impact on the phenolic composition of winegrapes and related wines. Even if attention has often been focused on other phenolics, a great number of studies have included phenolic acids because of their quantitative and qualitative modifications during dehydration-withering processes. A systematic review that provides a concise overview of the extensive literature available on this important topic is lacking. Scope and approach: This review identified 39 articles to answer the research question: What changes occur in phenolic acids after the withering process of winegrapes? The expected contribution of this systematic review is to have a full view of the worthwhile recent findings on these often-overlooked compounds to manage the technological process with new awareness and to find eventual weaknesses in this field to highlight new questions and research directions. Key findings and conclusions: The research yielded useful results for withering and winemaking management. Phenolic acids are well represented in certain special productions to be proposed as markers of wine authenticity. Hydroxycinnamic and hydroxybenzoic acids and their derivatives are often affected differently by the withering process. Their evolution during grape withering is a complex phenomenon that is affected by many varietal and technological variables. In particular, the withering conditions applied and grape genotype play an important role in the changing amounts of phenolic acids, but there is still much to be understood, especially related to the combined effect of both factors through genetic responses to environmental stresses and their respective chemical implications. Highlights: Phenolic acids are represented by hydroxybenzoic and hydroxycinnamic compounds Their evolution during withering involves a complex balance of different processes Concentration effect usually prevails in withered grapes increasing their contents Withering conditions and genetic regulation are relevant in determining the content Phenolic acids have been proposed as authenticity markers for icewines